Modern Theory of Capital Cost and Capital Structure by Brusov – Filatova – Orekhova (BFO Theory) for Companies, which Ceased to Exist at the Time Moment n - Brusov, P.N.; Filatova, T.V.; Orekhova, N.P.; Eskindarov, M.A.; Kulik, V.L. (Journal of Reviews on Global Economics, 2015)
Modern theory of capital cost and capital structure by Brusov – Filatova – Orekhova (BFO theory), which describes the companies of arbitrary age n in opposite to the perpetuity Modigliani – Miller theory, is applied for companies, which ceased to exist at the time moment n. The required modification of BFO theory has been done in the paper. Formula BFO-2 for calculation of dependences of weighted average cost of capital, WACC, on the company's of lifetime n, on leverage level L and on tax on profit rate t for companies, which ceased to exist at the time moment n has been derived. We analyze these dependences and compare them with the results of classical BFO theory which describes the companies of arbitrary age n. Comparing of results, obtained for companies as remaining in the market (BFO), as well as retired from the market (BFO-2) shows that dependence of the weighted average cost of capital WACC of companies on leverage level L, the company's lifetime (or age) n and the tax on profit rate t are qualitatively similar in nature, while, there are significant quantitative differences in these dependences: WACC for companies ceased to exist, always turns out to be higher than that of the companies that remain on the market (with the same parameters: leverage level L, the company's lifetime (or age) n and the tax on profit rate t, capital costs (equity and debt)), by other words the cost of attracting capital for companies that continue to operate, is always lower. We examine whether the effects, discovered by us within classical BFO theory, are present in its modified form (BFO-2). We have found that within trade off theory there is no an optimal capital structure for BFO-2 case as well as for BFO (as it has been proven by us before), while the qualitatively new effect in corporative finance (decreasing of equity cost with leverage L), existing within classical BFO theory, is absent in BFO-2 case similar to the case of perpetuity companies.